Pengaruh Harga Dan Kualitas Pelayanan Terhadap Loyalitas Pelanggan Pada PT Alakasa Extrusindo - Abdullah Abdullah; M. Rizan (Postgraduate of Jayabaya University, 2015)
The purpose of this research was to determined the effect of price on customer loyalty, to determine the effect of services quality on customer loyalty, as well as to determine the effect of price and service quality simultaneously on customer loyalty at PT. Alakasa Extrusindo employee. The method used in this research is an explanatory survey with type of descriptive and quantitative research, with a total sample 57 employee. The results provide empirical support for the proposed of significant effect partially price on customer loyalty, as significant effect partially of service quality on customer loyalty. Additionally, The result also showed that there are significant effect between price and service quality simultaneously on customer loyalty.The purpose of this research was to determined the effect of price oncustomer loyalty, to determine the effect of services quality on customerloyalty, as well as to determine the effect of price and service quality simultaneouslyon customer loyalty at PT. Alakasa Extrusindo employee.The method used in this research is an explanatory survey with type ofdescriptive and quantitative research, with a total sample 57 employee.The results provide empirical support for the proposed of significanteffect partially price on customer loyalty, as significant effect partiallyof service quality on customer loyalty. Additionally, The result alsoshowed that there are significant effect between price and service qualitysimultaneously on customer loyalty.